2011
DOI: 10.1111/j.1748-5827.2011.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the use of amiodarone in dogs with arrhythmias (from 2003 to 2010)

Abstract: Amiodarone may be an effective and safe alternative to treat supraventricular and ventricular arrhythmias in dogs, when common anti-arrhythmic drugs are not effective or contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In another study using client-owned dogs with supraventricular tachyarrhythmia, uncommon gastrointestinal side effects were attributed to oral amiodarone, and the clinical signals improved after the does was reduced to 5 to 7.5 mg/ day. The conclusion was that amiodarone could be a safe and effective alternative for the treatment of arrhythmias that are not controlled with other anti-arrhythmic drugs (PEDRO et al, 2012).…”
Section: Blood Chemistry Resultsmentioning
confidence: 99%
“…In another study using client-owned dogs with supraventricular tachyarrhythmia, uncommon gastrointestinal side effects were attributed to oral amiodarone, and the clinical signals improved after the does was reduced to 5 to 7.5 mg/ day. The conclusion was that amiodarone could be a safe and effective alternative for the treatment of arrhythmias that are not controlled with other anti-arrhythmic drugs (PEDRO et al, 2012).…”
Section: Blood Chemistry Resultsmentioning
confidence: 99%
“…Slow, non-sustained VT, also known as accelerated AV rhythm (<120 bpm), with no haemodynamic compromise, may resolve spontaneously and oftentimes does not require treatment 12. Conventional treatment of VT includes lidocaine (up to 8 mg/kg intravenous bolus, followed by a CRI of 50–80 μg/kg/minute CRI), esmolol, procainamide, amiodarone or magnesium 13 14. In this case, immediate identification of the cardiac or extracardiac source of VT would have been ideal for better VT-targeted management, but was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…A second ex vivo controlled study evaluating the effects of amiodarone on thyroid function test results identified inhibition of TSH‐induced secretion of T4 (73% of normal) and T3 (68% of normal) 148 . Finally, a retrospective study of dogs receiving amiodarone for treatment of arrhythmias found no change in serum TT4 and TSH concentrations after a median of 84 and 75 days of treatment, respectively 70 . Health status, study power and design, and amiodarone dose could account for the inconsistent serum TT4 results found between studies.…”
Section: Effects Of Drugs On Thyroid Functionmentioning
confidence: 98%